Pengembangan e modul interaktif pada mata pelajaran fisika kelas VIII SMP 40 Makassar - Sitti Asriani; Nurhikmah H (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was conducted by the researcher based on initial observations, where the researcher found that learning at SMP 40 Makassar had not yet developed technology-based learning and was still using printed textbooks. The objectives of this research development are: (1) To identify the level of development needs, (2) To design an e-module for the Physics subject, (3) To determine the validity level of the e-module, and (4) To determine the practicality level of the e-module. This research uses an R&D approach with the 4D development model (Define, Design, Develop, Disseminate). Data collection techniques used include questionnaires and documentation. The research was conducted with a total of 30 eighth-grade students and one physics teacher as the research subjects.The research results are as follows: (1) In the Planning Stage, through the needs identification process, it was found that students at SMP 40 Makassar need digital-based learning using e-modules. (2) In the Design Stage, development was carried out based on the information obtained, by determining and searching for objects to be developed in the e-module in the form of text, images, and videos. (3) In the Development Stage, the product trial began with an alpha test, which resulted in a valid instrument. The media expert gave an average score that fell into the "very good" qualification, and the content/material expert gave a score of 92%, which also fell into the "very good" qualification. Therefore, the media was tested in the field to determine its practicality. The beta test, conducted through small group trials, resulted in a score of 90.1%, which was classified as "very practical", while the large group trial yielded a score of 96%, also classified as "very practical". The response from the eighth-grade teacher was also in the "very practical” This research was conducted by the researcher based on initial observations, where the researcher found that learning at SMP 40 Makassar had not yet developed technology-based learning and was still using printed textbooks. The objectives of this research development are: (1) To identify the level of development needs, (2) To design an e-module for the Physics subject, (3) To determine the validity level of the e-module, and (4) To determine the practicality level of the e-module. This research uses an R&D approach with the 4D development model (Define, Design, Develop, Disseminate). Data collection techniques used include questionnaires and documentation. The research was conducted with a total of 30 eighth-grade students and one physics teacher as the research subjects.The research results are as follows: (1) In the Planning Stage, through the needs identification process, it was found that students at SMP 40 Makassar need digital-based learning using e-modules. (2) In the Design Stage, development was carried out based on the information obtained, by determining and searching for objects to be developed in the e-module in the form of text, images, and videos. (3) In the Development Stage, the product trial began with an alpha test, which resulted in a valid instrument. The media expert gave an average score that fell into the "very good" qualification, and the content/material expert gave a score of 92%, which also fell into the "very good" qualification. Therefore, the media was tested in the field to determine its practicality. The beta test, conducted through small group trials, resulted in a score of 90.1%, which was classified as "very practical", while the large group trial yielded a score of 96%, also classified as "very practical". The response from the eighth-grade teacher was also in the "very practical”